2014
DOI: 10.1002/lary.24691
|View full text |Cite
|
Sign up to set email alerts
|

Does post‐infectious olfactory loss affect mood more severely than chronic sinusitis with olfactory loss?

Abstract: 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…With regard to demographics, depression was associated with female sex in two studies, 8,19 whereas three studies failed to detect an association. 7,13,18 In general, other demographic factors, such as age and race, were uniformly not associated with depression.…”
Section: Factors Associated With a Positive Depression Screen Results mentioning
confidence: 94%
See 3 more Smart Citations
“…With regard to demographics, depression was associated with female sex in two studies, 8,19 whereas three studies failed to detect an association. 7,13,18 In general, other demographic factors, such as age and race, were uniformly not associated with depression.…”
Section: Factors Associated With a Positive Depression Screen Results mentioning
confidence: 94%
“…The first study used a validated Japanese version of the BDI-II, which was revised from the original BDI in 1996 to correspond with the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria. 19,20 A score of Ն10 was used to define depression, which resulted in a prevalence of mild depression to be 36%, moderate depression to be 4%, and severe depression to be 0%. The combined prevalence, therefore, was 40% ( Table 1).…”
Section: Systematic Review Of a Positive Depression Screen Results Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study using hospital anxiety and depression scale (HADS), 25.9% and 14.7% of CRS patients had high levels of anxiety and depression, respectively [8]. In a cohort study in 2011 the incidence of depression in patients with CRS was 77% more than control group with a hazard ratio of 1.56 [8] while these studies report depression as a highly prevalent disorder in CRS patients there are some other studies which report the prevalence of highly probable depression as low as 3 to 4% [9,10]. In 2016 Schloser et al reviewed 13 studies and reported the prevalence of probable depression to be from 11 to 40% [11].…”
Section: Introductionmentioning
confidence: 99%